2008
DOI: 10.1159/000151336
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Pregnancy with Nephrotic Syndrome due to Preexisting Membranous Glomerulonephritis: A Case Report

Abstract: The influence of membranous glomerulonephritis (MGN) on maternal and fetal outcome is controversial, as is the effect of pregnancy on the course of preexisting nephrotic syndrome. We report a case of successful management of a pregnancy with preexisting severe nephrotic syndrome due to biopsy-proven primary MGN. Our patient became pregnant in a non-compliance period, discontinued the nephrological follow-up program and her kidney disease decompensated. From the 22nd gestational week the patient was treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The least toxic immunosuppressive agents used to treat various diseases in pregnancy are azathioprine and cyclosporine. There are several reported cases regarding the treatment of MN in pregnancy, mainly with corticosteroids, which all ended either with preterm delivery or with early elective termination of pregnancy [5,10,11,12]. Cyclosporine used in post-transplant maintenance therapy may be used to treat some forms of glomerulonephritis in pregnancy, including MN [13].…”
Section: Discussionmentioning
confidence: 99%
“…The least toxic immunosuppressive agents used to treat various diseases in pregnancy are azathioprine and cyclosporine. There are several reported cases regarding the treatment of MN in pregnancy, mainly with corticosteroids, which all ended either with preterm delivery or with early elective termination of pregnancy [5,10,11,12]. Cyclosporine used in post-transplant maintenance therapy may be used to treat some forms of glomerulonephritis in pregnancy, including MN [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown good neonatal outcomes in patients with nephrotic syndrome, others have demonstrated foetal loss rates ranging from 24% to 35%. Most of these losses were attributed to first trimester spontaneous miscarriages [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…En caso de presentarse edema secundario a pérdida de proteínas como en el síndrome nefrótico durante el embarazo, se requeriría implementar un manejo más allá de la inmunosupresión. De forma conservadora el edema puede tratarse con elevación de miembros inferiores y compresión mecánica con medias de compresión, siendo necesario frecuentemente el uso de diuréticos de asa tipo furosemida o, en casos extremos, infusión de albúmina [1,43].…”
Section: La Valoración Preconcepcional Es La Piedra Angular Del éXito De La Gestación En Términos Generalesunclassified